Innovative Transformations of Ukraine's Public Administration on the Digital Instruments Development - Nataliia ORLOVA; Ivan DRAGAN; Tykhon YAROVOІ; Iuliia MOKHOVA (Communications of International Proceedings, 2021)
The article determines that the essential prerequisites for effective digital economy development in Ukraine are e-government and innovative technologies. The purpose of the paper is to study the innovative transformations in public administration in Ukraine in the context of digital tools and e-government development and implementation to a wide extend. The methodological basis of the study is data from the United Nations Development Program, Huawei Technologies, State Statistics Service of Ukraine, Information Impacts Magazine, Times Editions. The study highlights the innovative tools of e-government and proves the need for their widespread use to improve management efficiency. Methodological approaches to monitoring and analysis of the information society and e-government development have been summarised. Based on the digital trends analysis in Ukraine, it has been proved that applying a systematic approach and a unified information policy in the media field, informatisation and development of the information society, and information security allows for the most significant positive effect in public administration. The author reviews Ukraine's digital opportunities and digital barriers while developing these trends. It has been proved that digital transformation leads to the emergence of new unique systems and processes. The reform of any industry in modern conditions is aimed at the widespread use of innovative digital technologies. The author systematises the critical tasks for innovative digital transformations development in the primary sectors of Ukraine such as health, environment and natural resources, social protection, financial and budgetary policy, protection of human rights and freedoms, transport and infrastructure, regional development and reform of local government and territorial authority's management. It has been proved that their implementation will improve the quality of public services, increase their mobility and competitiveness. The areas of e-governance development that ensure innovative transformations and key measures for its enhancement have been identified, taking into account the benefits of innovative electronic tools for citizen involvement in governance processes.
Keywords: Public Administration; Innovation; Digital Tools; E-Government.